Study of the removal of methylene blue dye from aqueous solutions using in natura bamboo (Bambusa Vulgaris) as adsorvent. (Research, Society and Development, 2022)
Concerns about the environment and public health have driven the search for in natura adsorbents, called biosorbents, to be used in adsorption processes in the treatment of industrial effluents. The objective of this work was to study the efficiency of bamboo (Bambusa Vulgaris) in the in natura condition as an adsorbent in the removal of methylene blue from aqueous solution, as they have culms that can exceed 6 meters in height and 5 centimeters in diameter. For the kinetic tests, the samples were shaken and after appropriate intervals of contact time, aliquots were removed to determine their concentrations, the data obtained were analyzed according to the pseudo first order and pseudo second order kinetic models, as well as the material was characterized through Scanning Electron Microscopy (SEM) analysis. The results showed a second order adsorption kinetics, with a removal percentage around 90%, with an equilibrium time of 840 min, with an adsorptive capacity qe of 35.7 mg/g of adsorbent material. It was confirmed that the use of in natura bamboo as an adsorbent becomes an ecologically efficient technique in adsorption processes for the treatment of effluents containing this type of dye.